AL-IRSYAD MOVEMENT: A HADRAMI CONTRIBUTION IN SOCIAL AND EDUCATION ASPECTS IN TEGAL - Soekarba, Siti Rohmah; -, Rosyidah (International Review of Humanities Studies, 2020)
This article investigates Al-Irsyad contribution with transnational approach especially in tracing social cultural community of Indonesia in the context of Tegal. In this article, authors focus on Al-Irsyad established in 1914 by Ahmad Surkati (1876-1943) who had an important role in the Islamic reformation movement in the early twentieth century in Indonesia. His intellectual views and religion-politics stressing the equality of all Muslims. Protesting against the privileged position of the sayyids in Indonesia, he founded the new organization Jam’iyyat al-Irsyad which was to become a leading modernist organization. Al-Irsyad contribution in social and education aspects in Tegal becomes the discussion in this article. The authors used qualitative method by doing interview and observation. Deliar Noer said that social movement of Al-Irsyad is counted as an Islamic modern movement. The result of this research shows that Al-Irsyad movement gives positive contribution towards the society in social and education aspects in Tegal.